White wine (白酒 Báijiǔ) in worship at Tridharma temples - Indah Mauludina; Ayesa Ayesa; Tri Wahyu Retno Ningsih (Insights into Language, Culture and Communication, 2024)
This study aims to investigate white wine in various solemnities performed in Tridharma temples. The data were collected by observation, interview, and documentation. To obtain data, the informants were interviewed. The informants were one biokong and two worshippers of Tridharma temples. The total number of informants was six. Two Tridharma temples were chosen as the locations for conducting this research. It was Toa Se Bio Temple. As it is the oldest Tridharma temple in West Java, the writer chose it as the location of the study. The theory used in analyzing the data were Xiao’s theory (1995), a textbook entitled The Worshipper Leaders (2015), and a book entitled A Brief History of Sian Djin Ku Poh Temple (2019). The results revealed that white wine has been used in worship. It is used in worship toward ancestors and sinbengs. There were two kinds of the usage of white wine. The use of white wine in prayer activities is still valid, especially for prayer activities and festivals. As for prayer activities that still use white wine, namely prayers to worship sinbeng, Cap Go Meh night activities, and Sejit. The use of white wine in prayer activities is a tradition that has existed for generations. It is also used in tangsin ceremony, Cap Go Meh Eve, and sejit ceremony.   Received: 29 August 2023 Accepted: 06 January 2024 Published: 24 April 2024